Mathematics Learning Achievement with Snowball Throwing for Kinesthetic Learning Style Students - Ridam Dwi Laksono; Alsa Permata Yuniarti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
This activity examines students who have a variety of learning styles in conventional learning compared to snowball throwing learning in mathematics. This research was conducted with a quasi-experimental design. The population is students 2nd junior high school. The sample is determined by a random sampling technique. Learning styles observed is Visual, Auditory and Kinesthetic. Data were analyzed using ANOVA two unequal cell lines. the post ANOVA test using the Scheffe test. Student learning outcomes with snowball throwing are better. Student learning styles have an influence on learning achievement. Interaction occurs between learning models and student learning styles. Students with kinesthetic learning styles have achievements that are as good as students with two other learning styles in snowball throwing learning. Using questions and discussions during the learning process in snowball throwing can bring up a variety of spectrum of learning styles that students need in the learning process